A MODEL OF RELIGIOUS LIFE BASED ON THE MADINAH CHARTER FOR CHARACTER FORMATION OF STUDENTS IN MEDAN CITY - Alkausar Saragih, Nelvitia Purba, Rahmadi Ali (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2026)
This study aims to determine interfaith harmony in the Islamic version, as a religion that is a blessing for all creation. The Medina Charter, consisting of 47 articles, laid the foundations for the life of religious communities in a pluralistic and diverse nation, encompassing both ethnicity and religion. The Medina Charter specifically stipulates "Tolerance." The research, conducted using the Research and Development method, begins with the identification of potential or problems. To implement an effective, integrated model, pattern, or system for students that can be applied to foster mutual tolerance in religious life based on the Medina Charter, students at universities are provided with a Problem-Based Learning model. This research was conducted in Medan City, and a preliminary survey was conducted on the regional conditions. The population was determined and limited by random sampling.